Crystals at High Deformation Rates Displaying Glassy Behavior. Issue 8 (10th April 2019) - Rida, Ali; Micoulaut, Matthieu; Rouhaud, Emmanuelle; Makke, Ali
Abstract : When investigated as a function of deformation rate and time, model nano‐crystals exhibit a clear threshold in mechanical and relaxation behavior, this observation being valid in both the Hooke (elastic) and plastic regime. At low deformation rate ( ϵ ˙ < ϵ ˙ c ≃ 5 × 1 0 5 s − 1 ), materials are able to equilibrate with ongoing deformation, whereas ultra‐fast deformations bring the system out of equilibrium on the same nanosecond timescale. The time evolution of stress is investigated and suggests features that are typical of glassy relaxation with a stretched exponential behavior for stress relaxation that is only encountered for large deformation rates. Related relaxation times furthermore reveal a rapid increase with ϵ ˙ . These results actually link general aspects of plastic deformation, irreversibility and thermal equilibrium. Abstract : The influence of the strain rate on nanocrystalline material is investigated using molecular dynamics simulations. The application of large strain rates increases substantially the amount of disorder that displays relaxation phenomena typical of glassy materials. The stress‐time evolutions display a stretched exponential behavior that is found in viscous liquids. Also, the calculated relaxation times are larger than the simulations timescale which indicates that the system is falling out of equilibrium.